2011
DOI: 10.1002/app.35457
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the photochemical prevulcanization in a falling film photoreactor

Abstract: The photochemical prevulcanization of natural rubber (NR) latex via the thiol-ene reaction is a new approach aiming at the replacement of noxious processing agents used in conventional sulfur vulcanization processes (e.g., accelerators) together with cost saving options. The crosslinking reaction involves the excitation of a selected photoinitiator with ultraviolet (UV) light which is followed by the formation of thioether links due to the thiol-ene addition reaction. The photochemical process is carried out i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 38 publications
2
27
1
Order By: Relevance
“…It ensures short reaction times, ambient curing temperatures, and the substitution of noxious process chemicals that often elicit allergenic reactions of the human skin. As a consequence, UV crosslinked latex articles are characterized by good skin compatibilities and furthermore exhibit high tensile strengths 12–14…”
Section: Introductionmentioning
confidence: 99%
“…It ensures short reaction times, ambient curing temperatures, and the substitution of noxious process chemicals that often elicit allergenic reactions of the human skin. As a consequence, UV crosslinked latex articles are characterized by good skin compatibilities and furthermore exhibit high tensile strengths 12–14…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] UV induced thiol-ene chemistry is also used for the synthesis of functional polymers and the side-chain modification of polymers. [18] Low field 1 H multiple-quantum (MQ) solid-state NMR experiments revealed that thiol-ene elastomer networks exhibit homogenous networks with narrow spatial crosslink distributions and a low amount of short chain defects (<5%). [14][15][16] By employing multi-functional thiols, thiol-ene chemistry can also be applied to efficiently crosslink diene-rubber materials in liquid and solid state.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] This new photo-vulcanization technique facilitates the crosslinking of diene-rubbers under mild conditions and short reaction times. [18] Low field 1 H multiple-quantum (MQ) solid-state NMR experiments revealed that thiol-ene elastomer networks exhibit homogenous networks with narrow spatial crosslink distributions and a low amount of short chain defects (<5%). [19][20][21] While thiol-ene chemistry is of great value in the fabrication of functional elastomers, the convenient formation of uniform polymer networks with low shrinkage stress is a sought-after property in numerous applications, ranging from dental restoratives over advanced coatings to optical materials.…”
Section: Introductionmentioning
confidence: 99%
“…The photoreactor is a vertical glass column with a diameter of 13.5 cm and a length of about 1 m, with the source of the UV-A/B radiation emitted from one UVmercury lamp type T8 TL with a length of 1 ft, power of 3000 W, and irradiance of 1.1 W/cm 2 . This lamp is located in the middle of the glass column, as shown in Figure 2 Schlögl et al, 2012;Schlögl et al, 2014). The VNRLI process is carried out as follows: A thin layer (film) NRL is passed through the photoreactor wall using gravity at a flow rate of 1.3 liters/minute and then irradiated with a beam of UV-A/B photons derived from the UV-mercury lamp irradiators.…”
mentioning
confidence: 99%
“…The new technique of vulcanizing NRL with UV-A/B radiation has an advantage: it does not use a sensitizer, accelerator material such as dithiocarbamate and 2-mercapt-benzothiazole which are a high risk of cytotoxicity and tissue irritancies, or activators, so it is worth considering for further development in the manufacturing of surgical gloves Schlögl et al, 2012;Schlögl et al, 2014).…”
mentioning
confidence: 99%